A Meta-Analysis Informed Investigation into the Quantification of the NAD Metabolome in Mammalian Tissues - Azouaoui, Dassine (Université d'Ottawa / University of Ottawa, 2023)
This study investigates the in vivo effect of nicotinamide riboside (NR), a nicotinamide adenine dinucleotide (NAD) precursor, on the NAD metabolome of mouse tissues. In order to build a strong basis for this work, pre-analytical and analytical procedures used to measure NAD-related metabolites were examined and an LC-MS-based method was developed to study the NAD metabolome. The meta-analysis of published NAD(P)(H) quantification results from rodents and humans showed important discrepancies between studies regardless of the quantification method. Thereafter, a targeted NAD metabolomics protocol, including the preparation of yeast-derived stable isotope internal controls, was developed and used to confirm that NR oral supplementation increased the concentrations of most NAD-related metabolites in mouse liver and skeletal muscle with an important accumulation of degradation metabolites. Ultimately, this study provides new insight into the kinetics of oral NR supplementation and highlights the need for standardization in NAD quantification methods.
Keywords: Nicotinamide adenine dinucleotide; NAD+; LC-MS; Metabolomics; Nicotinamide riboside; Quantification methods; Metabolism